Metallic Magnetic Nanoparticles. (2005) - Hernando, A.; Crespo, P.; García, M. A.
Abstract : In this paper, we reviewed some relevant aspects of the magnetic properties of metallic nanoparticles with small size (below 4 nm), covering the size effects in nanoparticles of magnetic materials, as well as the appearance of magnetism at the nanoscale in materials that are nonferromagnetic in bulk. These results are distributed along the text that has been organized around three important items: fundamental magnetic properties, different fabrication procedures, and characterization techniques. A general introduction and some experimental results recently obtained in Pd and Au nanoparticles have also been included. Finally, the more promising applications of magnetic nanoparticles in biomedicine are indicated. Special care was taken to complete the literature available on the subject.